Translation of HDL circuit description to circuit netlist - Ma, Su Yamin (2008)
For a top-down system design, Hardware Description Language (HDL) is often used for high-level specification and behaviour simulations. Whereas for a bottom-up circuit design, the circuit designer will normally be dealing with device models for circuit simulation.